Left ventricular global longitudinal strain is associated with filling pressure and cardiac output in an outpatient setting: Insights from CardioMEMS™ - Francisco Barbas de Albuquerque; Rita Teixeira; Tiago Pereira-da-Silva; Vera Ferreira; António Valentim Gonçalves; Rita Ilhão Moreira; Ana Teresa Timóteo; Ana Galrinho; Luísa Branco; Pedro Rio; João Alves; Sofia Barquinha; et al. (Revista Portuguesa de Cardiologia)
Introduction and objectives: Left ventricular global longitudinal strain (LVGLS) is an indicator of myocardial function in patients with heart failure with reduced ejection fraction (HFrEF) and preserved ejection fraction (HFpEF). Nevertheless, it is not clear whether LVGLS correlates with filling pressures and cardiac output (CO) in an ambulatory setting. We aimed to assess whether LVGLS is associated with invasive pulmonary artery pressures (PAP) and CO in outpatients using the invasive remote monitoring CardioMEMS™ system. Methods: This single-center, prospective observational study included patients with HFrEF undergoing remote monitoring using the CardioMEMS™ system, between January 2020 and December 2022. Repeated transthoracic echocardiography (TTE) studies were performed in each patient and invasive hemodynamic data were obtained during the TTE studies using the CardioMEMS™ system. Univariate and multivariate models were used to assess the potential association between LVGLS and invasive PAP and CO. Results: Twelve patients were included and 46 TTE studies were analyzed. LVGLS was correlated with diastolic (d) PAP (r=0.403, p=0.041) and CO (r=−0.426, p=0.039) in the univariate analysis. In multivariate models, LVGLS was an independent predictor of dPAP and CO, but not mean PAP or systolic PAP. The variation of LVGLS between TTE studies was correlated with the variation of dPAP during follow-up (r=0.60, p=0.017). Conclusions: In a cohort of HFrEF patients under invasive hemodynamic remote monitoring, LVGLS was independently associated with invasive filling pressures and CO, in an outpatient setting. These findings reinforce the value of LVGLS for the management of outpatients with HFrEF. Resumo: Introdução e objetivos: O strain longitudinal global do ventrículo esquerdo (SLGVE) é um indicador de função miocárdica em doentes com insuficiência cardíaca com fração de ejeção reduzida (ICFEr) e com fração de ejeção preservada (ICFEp). No entanto, não é totalmente claro se o SLGVE se correlaciona com as pressões de enchimento e débito cardíaco (DC) no contexto ambulatório. Avaliámos a associação entre o SLGVE com as pressões (P) invasivas da artéria pulmonar (AP) e DC utilizando o sistema CardioMEMS™ de monitoração remota invasiva. Métodos: Este estudo unicêntrico, observacional e prospetivo incluiu doentes com ICFEr monitorados remotamente com o sistema CardioMEMS™, entre janeiro 2020 e dezembro 2022. Ecocardiograma transtorácicos (ETT) seriados foram executados em cada doente e os dados invasivos hemodinâmicos foram obtidos no momento de execução do ETT, usando o sistema CardioMEMS™. Modelos uni- e multivariados foram usados para avaliar a potencial associação entre o SLGVE e PAP e DC invasivos. Resultados: Doze doente foram incluídos e 46 ETT foram analisados. O SLGVE correlacionou-se com a PAP diastólica (r = 0,403, p = 0,041) e DC (r = −0,426, p = 0,039) na análise univariada. Nos modelos multivariados, o SLGVE foi um preditor independente da PAP diastólica e DC, mas não da PAP média e PAP sistólica. A variação do SLGVE entre ETT correlacionou-se com uma variação correspondente de PAP diastólica durante o seguimento (r = 0,60, p = 0,017). Conclusões: Numa coorte de doentes com ICFEr sob monitoração remota invasiva, o SLGVE está associado de forma independente com as pressões de enchimento e DC, no contexto ambulatório. Estes achados reforçam o valor do SLGVE na gestão dos doentes ambulatórios com ICFEr.